GAMBARAN PERILAKU PEMAKAIAN ZAT ADIKTIF PADA REMAJA AWAL - Azizah " "; Riri " Novayelinda; Darwin " Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The behavior in using of addictive substanceson teenager drastically increase every year and caused many health effects. The objective of this research is to know the Use of addictive substances behavior overview on early teenager. This research used descriptive retrospective with cross sectional approach. Data collected by distribute questionnaire from 152 respondents who are study at VII, VII, and IX grade at two schools. They are State Junior high school 15 and State Junior high school 3. The result of this research shows that most of the respondents are 13 years old. They start to abuse addictive substance because of friends’ influence, the other is individual factor with sub variable curiosity, the need of group acceptance, following tendency, looking for enjoyment and environment factor with sub variable unharmonious family, and social control with peer and society. This study suggest to whom it related especially teacher to increase prevention activity the behavior in using addictive substances, family and teenager  become focus intervention to prevent the use of addictive substance behavior through improving teenager roles, school health unit, family empowerment, health promotion, and health problem prevention. Key words: individual factor, environment factor, addictive user